Waste Management at Jatiya Kabi Kazi Nazrul Islam University: Current Status and Future Options - Khan, MNH (Journal of Environmental Science and Natural Resources, 2018)
The present study was conducted to measure waste production and its categories of JKKNIU, and find out its management options. Samplings were done in Student Hall, Teachers’ and officers’ dormitory, and central cafeteria of the University. Waste categories were organic, biodegradable, recyclable, inert materials etc. Major portion of the waste was organic biodegradable, about 65% of total waste. Waste are not being collecting and disposing properly due to unavailability of facilities, and this creating environmental pollution. Landfill, composting, and anaerobic digestion etc. could be use for proper management and to produce bio-gas and bio-fertilizer. Integrated waste management option would be better solution. J. Environ. Sci. & Natural Resources, 10(2): 171-176 2017